(untitled) (JURNAL PROTEKSI KESEHATAN, 2026)
Matoa bark (Pometia pinnata J.R. Forst. & G. Forst) has long been used traditionally as a remedy for various ailments such as fever, skin disorders, infections, and inflammation. This study aims to determine the total phenolic content and antioxidant activity of matoa bark extract obtained through successive maceration using n-hexane, ethyl acetate, and 96% ethanol. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and triterpenoids. The results showed that the 96% ethanol extract had the highest total phenolic content at 169.804 mg GAE/g, followed by the ethyl acetate extract at 97.647 mg GAE/g, and the n-hexane extract at 52.549 mg GAE/g. Antioxidant activity tested using the DPPH method indicated that the ethanol extract exhibited the strongest activity with an IC₅₀ value of 92.593 μg/mL (strong category), followed by the ethyl acetate extract at 121.695 μg/mL (moderate category), and the n-hexane extract at 187.393 μg/mL (weak category). This study shows the role of polar solvents in increasing antioxidant activity and total phenolic content.